A visual volumetric hydrogel sensor enables quantitative and sensitive detection of copper ions1. Issue 38 (11th May 2015) - Wu, Rui; Zhang, Shenghai; Lyu, Jitong; Lu, Fang; Yue, Xuanfeng; Lv, Jiagen
<x xml:space="preserve">Abstract</x> A volumetric sensor design enables the precise naked-eye readout of hydrogel volume changes for quantitative and sensitive detection of copper ions.